Transient Dexmedetomidine Bolus-Induced Excessive Urination Intraoperatively in a 68-Year-Old Male - Joseph A. McGuire; Summer A. Niazi; Daniel C. Sizemore (Case Reports in Anesthesiology)
Excessive urination can be a perioperative challenge for providers due to the possibility of secondary hypernatremia. Dexmedetomidine has previously been reported by several groups to induce a polyuric-like syndrome; however, the exact mechanism in humans remains unclear. In this report, we discuss a case of intraoperative, transient dexmedetomidine bolus-induced excessive urination and suggest a potential mechanism by which this may occur in a subset of the population.